Telomere length and mortality in the Ludwigshafen Risk and Cardiovascular Health study - Pusceddu, Irene; Kleber, Marcus E.; Delgado Gonzales de Kleber, Graciela; März, Winfried (PLOS ONE, 2018)
Introduction Short telomeres have been associated with adverse lifestyle factors, cardiovascular risk factors and age-related diseases, including cardiovascular disease (CVD), myocardial infarction, atherosclerosis, hypertension, diabetes, and also with mortality. However, previous studies report conflicting results. Objectives The aim of the present study has been to investigate the involvement of telomere length in all-cause and CVD mortality in subjects hospitalized for diagnostic coronary angiography of the Ludwigshafen Risk and Cardiovascular Health (LURIC) study. Methods Relative telomere length (RTL) was measured with a Q-PCR based method in 3,316 participants of the LURIC study. Age-corrected RTL was calculated as the ratio between RTL and age. Median follow-up was 9.9 years. Cox regression and Kaplan-Maier analyses were performed to evaluate the role of RTL for all-cause and cardiovascular mortality. Results RTL correlated negatively with age (r = -0.09; p<0.001). In surviving patients the correlation between age and RTL was statistically significant (r = -0.088; p<0.001), but not in patients who died during follow-up (r = -0.043; p = 0.20). Patients in quartiles 2-4 of RTL had a lower hazard ratio for all-cause mortality (HR:0.822; 95%CI 0.712-0.915; p = 0.008) and CVD-mortality (HR:0.836; 95%CI 0.722-0.969; p = 0.017) when compared to those in the 1st quartile. Adjustment for major cardiovascular risk factors did not change this result, however additional adjustment for age attenuated this effect. Patients in the 4th quartile of age-corrected RTL compared to those in the 1st quartile had a lower hazard ratio for all-cause mortality, even with adjustment for major cardiovascular risk factors. Conclusions The present study supports the hypothesis that short telomere length increases the risk of all-cause and CVD mortality. Age appears to be an important co-variate that explains a substantial fraction of this effect. It remains unclear whether short telomeres contribute directly to the increase in mortality or if they are simply a surrogate marker for other adverse processes of aging.
Gesehen am 14.10.2020